O extermínio na história do regime político brasileiro (1964- 2014): uma leitura biopolítica a partir de Giorgio Agamben - Luna, Moisés Saraiva de (2017)
In this dissertation, our research’s object is centered in the use of key concepts of camp, biopolitics, homo sacer and exception, under the form of extermination, especially consolidated after the last Brazilian military regime of 1964 in its permanent into the current democratic regime, in 2014. Our problem question can be formulated as follows: Is there a continuity of authoritarian policies in Brazil, after so many years of dictatorship, in relation to those excluded by the system? Those who are life-killing, but not sacrificable, through extermination as a paradigm of contemporary government? In this way, we start from the hypothesis that the Brazilian military regime, terminated in 1985, based on the National Security Doctrine and the biopolitical management of the Brazilian government historically considered, together with the practices still present, fifty years after the beginning that regime and three decades after its completion are reflected in a camp’s form as a modern biopolitical paradigm on the indolent and useless bodies of society, notably the poor and opponents of the regime. This hypothesis are supported by adaptive interpretation from the contributions of Homo Sacer, State of Exception, articles and interviews of Giorgio Agamben, into previous readings to the research, perceive the existence of traces of this theory that can be applied to Brazil: the existence of the camp as a modern biopolitical paradigm; the torture, extermination and enforced disappearance persisting’s practices; and, a true regime of permanent exception, with determinable time and space, on the population possibly converted as homini sacri. Therefore, the present dissertation will use a deductive approach methodology, together with a historicalcomparative procedure method and a bibliographic research technique to explain the current Brazilian situation. The organization of this work will be in three chapters: first, we determine the assumptions present in this work, presenting the Brazilian historicalpolitical antecedents’, the biopolitical archeology of the contemporary state and the agambenian conceptual discussions of homo sacer, camp, biopolitics and permanent exception. Next, we seek a definition of forced disappearance and extermination between the various key-concepts close to it, and delimit the practice and theory of dictatorship and democracy in relation to our key concepts. In the last part, we present the Brazilian biopolitical governance paradigm, the place of Agambenian camp execution and permanent extermination and the confrontations and uncertainties about the life-that-canbe- killed in Brazil. The objective is to present the historical-philosophical assumptions of the Military Dictatorship to the Six Republic, the institutional approach of homo sacer in the Brazilian State and the challenges and threats to democratic consolidation in Brazil. It concludes by confirming the hypothesis, partially to the focused period, converging the previous historical practice to the military regime for the analyzed period, at the same time that it points out ways and difficulties in the probability of expansion of this extermination.